Influence of Alcohol Content and Storage Conditions on the Physicochemical Stability of Spirit Drinks - Mateusz Różański; Katarzyna Pielech-Przybylska; Maria Balcerek (Foods, 2020)
The purpose of this study was to investigate the effects of alcohol by volume (ABV) and storage temperature on changes in the clarity of rye and plum distillates, and their content of volatile compounds. Distillates with initial ABVs of 93.26% v/v (rye distillate) and 82.03% v/v (plum distillate) were diluted with deionized water to 40, 50, and 70% v/v. The samples were stored in darkness at different temperatures (−18 °C, 0 °C, 8 °C, 20 °C) for 8 weeks. The results showed that reducing the alcohol content and storage temperature caused turbidity to increase. The samples prepared from rye distillate were characterized by significantly lower turbidity than those produced from plum distillate. The highest increase in turbidity in comparison to the controls was observed in the samples with 40% v/v alcohol content stored at a temperature of −18 °C. Storage of the rye and plum distillates samples at different temperatures resulted in changes to the concentrations of volatile compounds, i.e., lower levels of acetaldehyde and higher alcohols, and increased content of esters. However, the alcohol content and storage temperature had no statistically significant effect on methanol concentration.